Breast cancer: miRNAs monitoring chemoresistance and systemic therapy - Singh, Shivam; Saini, Heena; Sharma, Ashok; Gupta, Subhash; Huddar, V. G.; Tripathi, Richa (Frontiers in Oncology, 2023)
With a high mortality rate that accounts for millions of cancer-related deaths each year, breast cancer is the second most common malignancy in women. Chemotherapy has significant potential in the prevention and spreading of breast cancer; however, drug resistance often hinders therapy in breast cancer patients. The identification and the use of novel molecular biomarkers, which can predict response to chemotherapy, might lead to tailoring breast cancer treatment. In this context, accumulating research has reported micro-RNAs (miRNAs) as potential biomarkers for early cancer detection, and are conducive to designing a more specific treatment plan by helping analyze drug resistance and sensitivity in breast cancer treatment. In this review, miRNAs are discussed in two alternative ways-as tumour suppressors to be used in miRNA replacement therapy to reduce oncogenesis and as oncomirs to lessen the translation of the target miRNA. Different miRNAs like miR-638, miR-17, miR-20b, miR-342, miR-484, miR-21, miR-24, miR-27, miR-23 and miR-200 are involved in the regulation of chemoresistance through diverse genetic targets. For instance, tumor-suppressing miRNAs like miR-342, miR-16, miR-214, and miR-128 and tumor-promoting miRNAs like miR101 and miR-106-25 cluster regulate the cell cycle, apoptosis, epithelial to mesenchymal transition and other pathways to impart breast cancer drug resistance. Hence, in this review, we have discussed the significance of miRNA biomarkers that could assist in providing novel therapeutic targets to overcome potential chemotherapy resistance to systemic therapy and further facilitate the design of tailored therapy for enhanced efficacy against breast cancer.